Understanding organizations through language - Tietze, Susanne (Sage publications, 2003)
Offering a viable alternative to 'functional' approaches to communication based around the metaphor of 'webs of meaning' and which uses semiology as its theoretical bedrock. The authors provide examples and argue how and why this approach is useful in understanding communicative processes.